'Our Care through Our Eyes'. Impact of a co-produced digital educational programme on nurses' knowledge, confidence and attitudes in providing care for children and young people who have self-harmed: a mixed-methods study in the UK. Issue 4 (4th May 2017) - Manning, Joseph C; Carter, Tim; Latif, Asam; Horsley, Angela; Cooper, Joanne; Armstrong, Marie; Crew, Jamie; Wood, Damian; Callaghan, Patrick; Wharrad, Heather
Abstract : Objectives: (1) To determine the impact of a digital educational intervention on the knowledge, attitudes, confidence and behavioural intention of registered children's nurses working with children and young people (CYP) admitted with self-harm. (2) To explore the perceived impact, suitability and usefulness of the intervention. Intervention: A digital educational intervention that had been co-produced with CYP service users, registered children's nurses and academics. Setting: A prospective, uncontrolled, intervention study with preintervention and postintervention measurement, conducted at a large acute NHS Trust in the UK. Participants: From a pool of 251 registered children's nurses and 98 participants were recruited to complete the intervention (response rate=39%). At follow-up, 52% of participants completed the postintervention questionnaire, with 65% (n=33) of those reporting to have completed the digital educational intervention. Primary outcome measures: Attitude towards self-harm in CYP was measured using a 13-item questionnaire; knowledge of self-harm in CYP was measured through an adapted 12-item questionnaire; confidence in different areas of practice was measured through Likert Scale responses; self-efficacy for working with CYP who have self-harmed was measured through an adapted version of the Self-efficacy Towards Helping Scale; clinical behavioural intention was measured by the Continuing Professional Development Reaction Questionnaire. Semistructured interviews were undertaken with a purposive sample of participants. Results: For those who completed the intervention (n=33), improvements were observed in knowledge (effect size, ES: 0.69), confidence, and in some domains relating to attitudes (effectiveness domain-ES: 0.49), and clinical behavioural intention (belief about consequences-ES:0.49; moral norm-ES: 0.43; beliefs about capability-ES: 0.42). Qualitative findings suggest participants experienced skill development, feelings of empowerment and reflection on own practice. Conclusions: The effect of the intervention is promising and demonstrates the potential it has in improving registered children's nurse's knowledge, confidence and attitudes. However, further testing is required to confirm this.